2014
DOI: 10.1038/nrendo.2014.202
|View full text |Cite
|
Sign up to set email alerts
|

Gastric emptying and glycaemia in health and diabetes mellitus

Abstract: The rate of gastric emptying is a critical determinant of postprandial glycaemia and, accordingly, is fundamental to maintaining blood glucose homeostasis. Disordered gastric emptying occurs frequently in patients with longstanding type 1 diabetes mellitus and type 2 diabetes mellitus (T2DM). A complex bidirectional relationship exists between gastric emptying and glycaemia--gastric emptying accounts for ∼35% of the variance in peak postprandial blood glucose concentrations in healthy individuals and in patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
208
2
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 216 publications
(225 citation statements)
references
References 207 publications
1
208
2
7
Order By: Relevance
“…Interestingly, none of the demographic characteristics was found to be significantly associated with delayed gastric emptying in the present cohort. Although diabetes is a recognized risk factor for gastroparesis, this is restricted mainly to patients with poorly controlled insulin‐dependent diabetes10. In the present study, only one of 15 patients with diabetes was insulin‐dependent, and most had adequate glycaemic control.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Interestingly, none of the demographic characteristics was found to be significantly associated with delayed gastric emptying in the present cohort. Although diabetes is a recognized risk factor for gastroparesis, this is restricted mainly to patients with poorly controlled insulin‐dependent diabetes10. In the present study, only one of 15 patients with diabetes was insulin‐dependent, and most had adequate glycaemic control.…”
Section: Discussionmentioning
confidence: 72%
“…There is no consensus definition across these tests10. Nuclear scintigraphy has been the test used most commonly11, although a recent study12 suggested that endoscopic evidence of food retention following routine fasting closely correlates with severe delayed gastric emptying on nuclear scintigraphy.…”
Section: Introductionmentioning
confidence: 99%
“…Intuitively, once-or twice-daily administration of 'short-acting' preparations of GLP-1 agonists, such as exenatide and lixisenatide, which predominantly diminish postprandial glucose by slowing GE [45,46], may have greater efficacy than once-weekly administration of longer-acting drugs, such as liraglutide and modified-release exenatide, where the slowing of GE appears to be modest with chronic use [45,46]. In summary, in healthy older individuals and patients with type 2 diabetes, acute i.v.…”
Section: Discussionmentioning
confidence: 99%
“…Another theory is that more thorough mastication (i.e. longer chewing time) and swallowing a food bolus with fine particles (< 2,000 μm) may delay gastric emptying and thus reduce postprandial glycaemia [6,30,32]. A bolus with finer particles reduces the viscosity of gastric content and increases pyloric outflow, thus increases sedimentation of solids in liquids and promotes the ability of antrum to preferentially empty liquids faster than solids [29].…”
Section: Discussionmentioning
confidence: 99%